THE ROLE OF THE WORLD OF EDUCATION IN MAINTAINING THE CIREBON LOCAL TRADITION (PERAN DUNIA PENDIDIKAN DALAM MENJAGA TRADISI LOKAL CIREBON) - Sarip, Sarip; Fadhli, Harun; Siswoyo, Siswoyo; Aulyah, Feny (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
Difficulties as well as challenges for Cirebon education in developing local traditions are faced with the development of religious understanding and globalization. Examples of earth charity and Cirebon nadran as a manifestation of gratitude for the gifts that have been given to humans on earth. The alms tradition of the earth and the Cirebon nadran are in line with the commemoration of international earth day which is commemorated every April 22nd. Religious ideology is often expressed in the practice of seemingly squandering costs which the community considers bid'ah and some are not bid'ah by reason of guarding the ancestral heritage of Cirebon. The problem that arises is how to maintain the local tradition of Cirebon amid religious understanding and globalization in order to be maintained and in line with the mandate of national education. The goal to be achieved in writing is to maintain, maintain and preserve the local traditions of Cirebon through school education. The benefits of giving enlightenment regarding religious understanding in Cirebon in seeing local traditions in Cirebon and providing solutions to the challenges faced by the world of national education in general. The method used is by describing words in the form of sentences regarding local traditions and challenges, team experience is used to explore information relating to the problem. Using Ghoethe's thinking about the search for novelty lies in ancient truth as a knife of analysis in terms of problem solving. As a result, the Cirebon local tradition has increasingly lost its identity due to the growing religious understanding in Cirebon and unstoppable globalization. Then we need support and synchronization between the goals of education, religious understanding and the challenges of globalization Kesulitan sekaligus tantangan bagi pendidikan Cirebon dalam mengembangkan tradisi lokal dihadapkan pada perkembangan paham keagamaan dan globalisasi. Contoh sedekah bumi dan nadran Cirebon sebagai perwujudan bentuk syukur atas karunia yang telah diberikan pada manusia di muka bumi. Tradisi sedekah bumi dan nadran Cirebon sejalan dengan subtansi peringatan hari bumi internasional yang diperingati setiap tanggal 22 April. Faham keagamaan sering dilontarkan pada praktik yang terkesan menghambur-hamburkan biaya yang kemudian masyarakat menganggapnya bid’ah dan sebagian lagi bukan bid’ah dengan alasan menjaga warisan leluhur Cirebon. Permasalahan yang timbul adalah bagaimana menjaga tradisi lokal Cirebon ditengah pemahaman keagamaan dan globalisasi agar tetap terjaga dan sejalan dengan amanah pendidikan nasional. Adapun tujuan yang hendak dicapai dalam penulisan adalah menjaga, mempertahankan, dan melestarikan tradisi lokal Cirebon melalui pendidikan sekolah. Manfaatnya memberikan pencerahan berkenaan dengan paham keagamaan di Cirebon dalam melihat tradisi-tradisi lokal di Cirebon dan memberikan solusi terhadap tantangan-tantangan yang dihadapi dunia pendidikan nasional pada umumnya. Cara yang digunakan yakni dengan mendeskripsikan kata dalam bentuk kalimat berkenaan dengan tradisi lokal dan tantangannya, pengalaman tim digunakan untuk menggali informasi yang berkenaan dengan permasalahan. Menggunakan pemikiran Ghoethe tentang pencarian akan kebaruan terbetik pada kebenaran kuno sebagai pisau analisis dalam kerangka pemecahan permasalahan. Hasilnya tradisi lokal Cirebon semakin kehilangan jatidirinya yang disebabkan oleh pemahaman keagamaan yang berkembang di Cirebon dan globalisasi yang tidak terbendung. Maka diperlukan dukungan dan sinkronisasi antara tujuan pendidikan, paham keagamaan dan tantangan globalisasi